Physical activity and health-related quality of life of patients with chronic knee pain after total knee replacement: analysis of the PEP-TALK trial - Fabiano, G; Smith, TO; Parsons, S; Ooms, A; Dutton, S; Fordham, B; Hing, C; Lamb, S; Pinedo-Villanueva, R (Elsevier, 2023)
Background: Chronic pain is a major challenge for some people after total knee replacement (TKR). The changing impact of this complication during the first post-operative year remains unclear. This analysis aimed to examine how physical activity and health-related quality of life (HRQoL) evolved over the first year after TKR for patients with and without post-operative chronic knee pain.